Telephone-Based Reeducation of Drug Administration for Helicobacterpylori Eradication: A Multicenter Randomized Controlled Study - Yan Zhao; Mudan Ren; Xin Wang; Guifang Lu; Xinlan Lu; Dan Zhang; Shuixiang He (Gastroenterology Research and Practice)
Poor adherence to treatment instructions may play an important role in the failure of Helicobacter pylori eradication. The aim of this study was to evaluate the effects of telephone-based reeducation on 14-day quadruple H. pylori eradication therapy. In total, 162 patients were randomly assigned (1 : 1) to either the intervention group (patients received telephone-based reeducation on the 4th, 7th, and 10th days of the course) or the control group (patients received instructions only at the time of getting the prescriptions). All patients received a 14-day quadruple H. pylori eradication therapy. The primary outcome was the H. pylori eradication rate. The secondary outcomes included the symptom relief rates and the incidence rates of adverse events. Seventy-five patients in the reeducation group and 74 patients in the control group completed the follow-up. The H. pylori eradication rate in the reeducation group was statistically higher than that in the control group (intention-to-treat: 72.8% vs. 50.6%, P=0.006; per-protocol: 78.7% vs. 55.4%, P=0.003). However, the symptom relief rates and the adverse event rates in these two groups were not significantly different. Overall, the results from this study suggest that telephone-based reeducation can be potentially applied to improve the H. pylori eradication rate in clinical practice, without significantly increasing the adverse effects.